Analysis of organic and elemental carbon in heating and non-heating periods in four locations of Beijing. Issue 1 (2nd January 2016) - Sun, Fengbin; Lun, Xiaoxiu; Liu, Xuhui; Mo, Li; Li, Renna; Zhang, Hongxia; Chen, Jungang; Cao, Yingying; Shi, Fangtian; Yu, Xinxiao
Abstract : The concentrations of elemental carbon (EC) and organic carbon (OC) in PM2.5 atmospheric aerosol were measured at four different sites in Beijing: Beijing Olympic Forest Park (OF), Jiufeng National Forest Park (JF), Beijing Forestry University campus lawn (G), and roads near the Beijing Forestry University (S). The winter heating period concentrations were 30–45% higher than the spring non-heating period. Possible reasons for this could be the severe convective weather in spring due to the temperate monsoon, deposition of PM2.5 to plants in spring, stable atmospheric conditions in winter, and/or a greater number of sources of carbonaceous aerosols in winter. The proportion of total carbon (i.e. EC + OC) in PM2.5 in Beijing is high. The OC/EC value was 2.45 (OF) and 2.39 (JF) in winter and 1.6 (OF) and 1.43 (JF) in spring. These ratios and the high correlation of OC with EC in the winter samples indicate a strong primary source of OC. Eight carbon fractions from the four different sampling locations were analysed, and the OC1–4 values were found to vary considerably. In winter, the OC1 values from all four sites were higher than the spring values. Although there were differences at each site, the percentages of OC2, OC3, EC1-OP, and EC2 were the largest. Secondary organic carbon (SOC) formed during long-range transport from the emission sources to the monitoring sites, and the increase of OC2 and OC3 concentrations could be associated with SOC.